Strengthening Mangrove Conservation Through Collaborative Governance: A Public Administration Perspective from Coastal Communities - Nasution, Mimin Sundari; Rusli, Zaili; Heriyanto, Meyzi; Mayarni, Mayarni; Zulkarnaini, Zulkarnaini (Universitas Sultan Ageng Tirtayasa, 2025)
Mangrove conservation is essential for enhancing coastal resilience with sustainable development, particularly in areas vulnerable to environmental degradation. This study explores the many factors that influence sustainable mangrove management from both a collaborative governance and public administration perspective. Using a quantitative approach with potential analysis and the MICMAC method, data were collected through expert sampling involving stakeholders with extensive knowledge in environmental policy and coastal governance. The analysis revealed four key enabler variables—stakeholder engagement, regulatory framework, economic conditions, and environmental awareness—all of which showed high influence with low dependency, thus positioning these variables appropriately as critical elements for establishing an effective green governance system. In addition, elements such as environmental education, institutional quality, law enforcement, socio-cultural values, technological innovation, and tourism potential were considered to contribute to long-term sustainability, but with less weighting. Integration and strengthening of these planned enablers remain essential to improving mangrove conservation outcomes, as well as ensuring the long-term well-being of coastal communities. This study highlights the importance of how we should foster a collaborative multi-actor governance model. This will support sustainable coastal ecosystem management within a public administration framework.